T.A.C – Conduct adjustment term according to the wording given by complementary law No. 68 of the state of Rondônia (Research, Society and Development, 2022)
The expression, Term of Conduct Adjustment -TAC is an agreement entered into between the parties involved with the purpose of protecting rights of a trans-individual nature. It is considered as an extrajudicial enforceable instrument that includes at least an obligation to do or not to do, what was agreed, and in case of non-compliance, the corresponding commission ensues. In view of this, this article aims to explore the application of the TAC to the public servant of the State of Rondônia, based on Complementary Law 68/92, in accordance with Complementary Law 993/2018. The methodology used was exploratory and descriptive, in which the data were supported by a literature review on government websites, still with a qualitative-comparative approach. Finally, discursive textual analysis was used. The TAC was incorporated into the Brazilian legal system through art. 211 of Law 8.069/90. Then the art. 113 of Law 8.078/90 expanded its application in § 6 to art. 5 of the Public Civil Action Law. The wording given by Complementary Law No. 68 of the State of Rondônia inserted in 2018 the procedures for the application of the TAC in accordance with Complementary Law 993/2018. The valued term was included as an important step in the improvement of disciplinary management within the State Public Administration, because, in addition to causing a significant gain in efficiency, it allows the rationalization of efforts in the investigation of faults whose low offensiveness points to the unnecessary deflagration. of bureaucratic punitive procedures.